Nilai Ekonomi Ekosistem Laguna di Negeri Ihamahu, Pulau Saparua, Kabupaten Maluku Tengah - Gea, Liyatin; Mishbach, Imam; Tuhumena, Lolita; Pirhel, Pirhel (Jurnal Kelautan, Lingkungan, dan Perikanan, 2023)
The existence of ecosystems in the water lagoon of Ihamahu Country has an important role for the people of Ihamahu Village. The study was conducted on July 17, 2020 with primary and secondary data collection. The sampling method used is purposive sampling a total of 10 people. The people of Iamahu Village always catch marine life in the Laguna ecosystem and its surroundings with used several fishing gear. Then, total economic value of Laguna ecosystem at Iamahu Village amount Rp 183.189.557 with used direct as Capture Fisheries and research activities amount Rp 45.620.000. Indirectly the benefits of coral reef ecosystems in Ihamahu waters for absorbs carbon content amount Rp 98.156.407. After that, option value amount Rp 471.150 an values that represent the usefulness of coral reef ecosystems (in laguna) at the future will be good directly or indirect, existence value through Contingent Valuation Method (CVM) amount Rp 34.380.000, and Inheritance Value Rp 4.562.000,-.